Mesoscopic time-dependent behavior of rocks based on three-dimensional discrete element grain-based model. (May 2020) - Fu, Teng-Fei; Xu, Tao; Heap, Michael J.; Meredith, Philip G.; Mitchell, Thomas M.
Abstract: A three-dimensional discrete element grain-based stress corrosion model incorporating the theories of subcritical crack growth and chemical reaction rate was built to explore the time-dependent behavior of damage evolution and fracture patterns of brittle rocks on a mesoscopic scale. The model was first validated and the model accurately captured the evolution of damage (tensile and shear microcracks) on the mesoscopic scale and the macroscopic mechanical behavior (the strength, and failure patterns) observed in laboratory experiments. The subcritical parameters of the model were calibrated to match the time-dependent damage deformation behavior observed in laboratory experiments. The time-dependent numerical results replicated the typical decelerating-accelerating axial strain behavior seen in laboratory brittle creep experiments. The crack propagation pattern in the simulation indicated that tension cracks were dominant. The results of numerical simulation showed that the time-to-failure during brittle creep decreased with the increase of the stress level, while the initial strain value, initial damage value, and minimum creep strain rate increased, as observed previously in the laboratory. We conclude therefore that the presented model supports a rich set of grain-scale discontinuities that can be related to microstructural features and provides a deeper understanding of the evolution of time-dependent damage on the mesoscale.